Product Differentiation Strategy at Nhanas Donuts Pinrang in Facing Culinary Business Competition in the Millennial and Gen Z Era - Kurniawaty; Yusrianti; Damayanti Trisnasari; Yayuk Astuti (Economics and Business Journal (ECBIS), 2026)
This study aims to analyze the product differentiation strategy implemented by Nhanas Donuts Pinrang in facing culinary business competition in the millennial and Gen Z era. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. Informants consisted of the owner, production and service employees, as well as millennial and Gen Z consumers. The results showed that the product differentiation strategy applied includes four main aspects: flavor innovation with contemporary variants (matcha cheese, red velvet crumble, cookies and cream), attractive and "instagrammable" visual display, aesthetic and modern packaging design, as well as active digital marketing through Instagram, Facebook, and TikTok. Supporting factors for the success of differentiation include the owner's creativity, understanding of young consumer behavior, strategic location, and digital branding. The implications of this study indicate that product differentiation integrated with digital marketing is able to increase competitiveness and customer loyalty of local culinary Micro, Small, and Medium Enterprises in the digital era.